MENUMBUHKAN MINAT LITERASI MELALUI PERMAINAN KEAKSARAAN DI TBM RUMAH BACA BUAHATI - Musrifah Musrifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
This service project aims to explore the interest in literacy in early childhood and provide assistance so that this interest grows into a literacy habit that can support the learning process and child development. The author conducted a service learning method with direct observation and involvement in the teaching and learning process at Taman Baca Masyarakat (TBM) Rumah Baca Buahati in Paciran Village, Lamongan Regency. The author found children's great interest in literacy games and picture books that successfully boosted children's literacy interest at TBM Rumah Baca Buahati. Children who actively play literacy games and regularly interact with picture books are encouraged to be interested in books and more skilled in reading books.